Plan de negocios para la producción y exportación de licor artesanal hecho a base de caña de azúcar tri destilada hacia la ciudad de Hamburgo, Alemania - Bosmediano Benalcázar, Cristóbal Doenitz (2019)
This document contains systematic and concentrated information on the business idea of producing and marketing tri distillated liquor to the German market, specifically the city of Hamburg. The product will be sent to its destination by means of maritime transport, in year 1, 250 boxes of 12 bottles are exported monthly and in year 5 the project will send monthly shipments of 266 boxes per month. In relation to the name chosen to represent the liqueur distilled tri is PUROEC, which represents the essence of the liquor and allows communicating its main strength that is its natural ingredients. The organizational structure has a high concentration in the activities that generate added value to the company, which is the production of the liquor and its export logistics to the city of Hamburg. The value proposition of PUROEC is to satisfy the need of German consumers to delight their palate with an artisanal liquor made from sugar cane and perfumed with tropical, this makes it possible to differentiate from the flavor of other liqueurs that They concentrate on fruits such as apples and grapes, which exist in the European market. The main recommendation for the project is to align the strategic objectives formulated in the organizational philosophy with the generation of early warning indicators, under the condition and specifications of the balanced scorecard, in this way; it is possible to align the obtaining of business results with the generation of information in the operational activities.